Bahasa Inggris - Kevin Lim (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
Background: Depression is a mood disorder that causes loss of motivation to stay or to do daily activities. Research on depression prevalence indicates that approximately 4.4% of the worldwide population suffers it. The mechanism in which depression occurred due to fast foods is the excessive fat content disturbs neurogenesis in the brain. This research is carried out to look into the connection among fast food intake with the incidence of depression. Method: An analytical study with a cross-sectional design is the method chosen to conduct this research. The samples include college students from the Faculty of Medicine in University of Sumatera Utara admitted in 2018 and acquired with total sampling. The tools used in this research were the CES-D and FFQ questionnaire. Results: The incidence of depression among applicants in 2018 was 48.3%.The statistical calculations indicates that there is a significant relationship between fast food consumption and depression (p=0,043); but not significant to family income (p=0,684) and physical activity (p=0,289). Conclusion: Excessive consumption of junk food can increase the risk of depression.